Analisis Penerimaan dan Kesuksesan Aplikasi M-health pada Lansia menggunakan Model UTAUT dan Delone & McLean - Merdekawati, Utami; Nugraheni, Dinar Mutiara Kusumo; Nurhayati, Oky Dwi (Jurnal Sistem Informasi Bisnis, 2024)
M-health plays a crucial role in providing medical services through features like online doctor appointments. While it offers convenience, there are challenges in its adoption among the elderly. The success of M-health depends on user acceptance and continued use. Therefore, an evaluation of information technology focused on the elderly in Indonesia is necessary. Technology accepted by users is not necessarily successful, and vice versa. This study aims to identify factors influencing the acceptance and success of M-health applications among the elderly. It combines the UTAUT and Delone & McLean models to investigate acceptance and success factors. The variables used are performance expectancy, effort expectancy, information quality, system quality, service quality, user satisfaction, and continuance intention. The PLS-SEM method is used to process respondent data. Analysis result shows that 61.6% of elderly users' satisfaction with M-health is influenced by information quality, service quality, performance expectancy, and effort expectancy. Meanwhile, 59.4% of the continuance intention is influenced by user satisfaction. This indicates that the application is well received and successful because it provides a satisfying experience. This study confirms that the combination of the UTAUT and Delone & McLean models is adequate.